The impact of COVID-19 outbreak and lockdown on maternal complications during pregnancy - Ghazal, Kariman; Hasan, Jihad El; Hijasi, Hanine; Khayrallah, Maysalloun; Sinno, Loubna; Koulaymi, Eva (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The COVID-19 outbreak has affected pregnant women. The aim of this study was to examine the effect of COVID-19 outbreak and lockdown on maternal complications in pregnant women. Methods: A retrospective review of pregnant patients who presented for antenatal care to the private clinic in Beirut, Lebanon before or during the COVID-19 lockdown which started in March 2020. The first group consisted of women before the lockdown between September 1, 2019 and February 29, 2020. The second group included women during or after the lockdown between March 1, 2020 and August 31, 2020. Results: A total of 97 women were included, 48 in the before lockdown group and 49 during or after lockdown group. The percentage of epigastric pain was significantly lower in the first group (12.5% vs. 71.4% respectively, p-value<0.0001). Anemia was significantly lower in the before group (60.4% vs. 83.7%, respectively p-value=0.01). Vomiting and hypotension were significantly higher in the after group. Around 87% of women in the before group had flu-like symptoms such as muscle ache and dizziness compared to 44.9% and 46.9% in the after group (p-value<0.0001). None of the patients in the after group visited the emergency department or were hospitalized during pregnancy. Almost 43% of patients in the after group had severe anxiety compared to 14.6% in the before group (p-value=0.001). Conclusions: Lockdown influenced maternal complications during pregnancy and resulted in anxiety for many women. Management practices regarding pregnancy and childbirth after lockdown are necessary to minimize the associated negative consequences.